2017
DOI: 10.1016/j.accfor.2017.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Watchdogs, helpers or protectors? – Internal auditing in Malaysian Local Government

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that: • a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 95 publications
1
22
0
6
Order By: Relevance
“…Furthermore, longitudinal research could inform whether the differences in the IA approaches to risk culture elaborated in this study will continue to exist or whether a new dominant approach will prevail over all other approaches. Third, since many studies provide evidence on IA being an ethically compromised governance practice (Everett and Tremblay 2014;Ferry et al 2017;Roussy 2013;Roussy and Rodrigue 2016), it could be important to understand how an ethically compromised IA could assure and consult on risk culture and ethical issues. Consequently, we also promote further studies on the ethical dilemma faced by internal auditors in carrying out risk culture or ethics audit.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, longitudinal research could inform whether the differences in the IA approaches to risk culture elaborated in this study will continue to exist or whether a new dominant approach will prevail over all other approaches. Third, since many studies provide evidence on IA being an ethically compromised governance practice (Everett and Tremblay 2014;Ferry et al 2017;Roussy 2013;Roussy and Rodrigue 2016), it could be important to understand how an ethically compromised IA could assure and consult on risk culture and ethical issues. Consequently, we also promote further studies on the ethical dilemma faced by internal auditors in carrying out risk culture or ethics audit.…”
Section: Resultsmentioning
confidence: 99%
“…Confirmation results with ASB revealed that the role of the Vice Director for supervision and control was limited. Those effective's supervision declined in line with the complexity and operational capacity of the bank (Ferry et al, 2017) Internal auditors' pattern in Islamic banks can be divided into two positions: supervisory directors' role and the role of separate internal control units. Both practices have the same role in controlling business risk in operational dimensions, financial statements, and management compliance, but with different intensities.…”
Section: Resultsmentioning
confidence: 99%
“…Behind all of that, there are critical concerns that the development of Islamic banking is just a euphoria, pseudo and dangerous if it is not based on an adequate institutional and regulatory framework from the aspect of Islamic banking best practices (Darmadi, 2013;Surbakti, 2004). The inadequate regulatory framework is most susceptible to various crime and fraud that has always threaten the national banking industry (Ferry, Zakaria, Zakaria, & Slack, 2017;Surbakti, 2004) Institutionally, there are sharia banks in the form of a full sharia bank (fullfledged) and some types of sharia business unit (Unit Usaha Syariah-UUS) within conventional banks, and sharia rural bank (Bank Perkreditan Rakyat Syariah-BPRS). Specifically, the research was focused on sharia rural banks, suggesting an exciting phenomenon; first, it represents small sharia banks in Indonesia, limited by size, capital, and location (Adnan & Muhammad, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Berdasarkan Tabel 2, nilai 2logL dari block 0 yang awalnya152,761 menja di 142,590 pada block 1, penurunan 2logL sebesar 10,171 tersebut berarti tambahan variabel bebas ke persamaan dapat mening katkan model fit dan juga memperbaiki model regresi (Christensen, Elder, & Glo ver, 2015;Dyckman & Zeff, 2014 (Ferry, Zakaria, Zakaria, & Slack, 2017;Fitzgerald & Giroux, 2014;Kirk, Brower, & Duncan, 2017). Bah kan, kebijakan dan komitmen publik dapat dianalisis melalui pendekatan dan rerangka agen dan prinsipal (An & Kweon, 2017;Vi ning & Richards, 2016).…”
Section: Hasil Dan Pembahasanunclassified